Short term olfactory memory and olfactory function after inhalation anesthetic agents: a randomized clinical trial - Sari,Huseyin (2020)
Abstract Background and objectives: This clinical trial aimed to evaluate the effects of two different inhalation anesthetic agents on postoperative olfactory memory and olfactory function in patients who underwent micro laryngeal surgery. Methods: This randomized prospective controlled study consisted of 102 consecutive patients with a voice disorder. The patients underwent micro laryngeal surgery for voice disorders under general anesthesia. Patients who did not meet inclusion criteria and/or declined to participate (n = 34) were excluded from the study. Patients were divided into two groups. Four patients from Group 1 and four patients from Group 2 were lost to follow-up. Group 1 (n = 30) received sevoflurane, and Group 2 (n = 30) received desflurane during anesthesia. We compared the results by performing the pre-op and post-op Connecticut Chemosensory Clinical Research Center Olfactory test. Results: Thirty-three patients (55%) were male and 27 (45%) were female. The mean age was 48.18 ± 13.88 years (range: 19‒70 years). Preoperative and postoperative olfactory functions did not show a significant difference within the groups postoperatively (p > 0.05). Preoperative and postoperative olfactory memory showed a significant decrease 3 hours after the surgery (p < 0.05). Conclusions: Olfactory functions and memory were not affected by desflurane in the early postoperative period. Although sevoflurane did not affect olfactory functions, it had a temporary negative effect on olfactory memory in the early postoperative period.